RAF1–MEK/ERK pathway‐dependent ARL4C expression promotes ameloblastoma cell proliferation and osteoclast formation. Issue 1 (16th November 2021) - Fujii, Shinsuke; Ishibashi, Takuma; Kokura, Megumi; Fujimoto, Tatsufumi; Matsumoto, Shinji; Shidara, Satsuki; Kurppa, Kari J; Pape, Judith; Caton, Javier; Morgan, Peter R; Heikinheimo, Kristiina; Kikuchi, Akira; et al.
Abstract: Ameloblastoma is an odontogenic neoplasm characterized by slow intraosseous growth with progressive jaw resorption. Recent reports have revealed that ameloblastoma harbours an oncogenic BRAF V600E mutation with mitogen‐activated protein kinase (MAPK) pathway activation and described cases of ameloblastoma harbouring a BRAF V600E mutation in which patients were successfully treated with a BRAF inhibitor. Therefore, the MAPK pathway may be involved in the development of ameloblastoma; however, the precise mechanism by which it induces ameloblastoma is unclear. The expression of ADP‐ribosylation factor (ARF)‐like 4c (ARL4C), induced by a combination of the EGF–MAPK pathway and Wnt/β‐catenin signalling, has been shown to induce epithelial morphogenesis. It was also reported that the overexpression of ARL4C, due to alterations in the EGF/RAS–MAPK pathway and Wnt/β‐catenin signalling, promotes tumourigenesis. However, the roles of ARL4C in ameloblastoma are unknown. We investigated the involvement of ARL4C in the development of ameloblastoma. In immunohistochemical analyses of tissue specimens obtained from 38 ameloblastoma patients, ARL4C was hardly detected in non‐tumour regions but tumours frequently showed strong expression of ARL4C, along with the expression of both BRAFV600E and RAF1 (also known as C‐RAF). Loss‐of‐function experiments using inhibitors or siRNAs revealed that ARL4C elevation depended on the RAF1–MEK/ERK pathway in ameloblastoma cells. It was also shown that the RAF1–ARL4C and BRAFV600E–MEK/ERK pathways promoted cell proliferation independently. ARL4C‐depleted tumour cells (generated by knockdown or knockout) exhibited decreased proliferation and migration capabilities. Finally, when ameloblastoma cells were co‐cultured with mouse bone marrow cells and primary osteoblasts, ameloblastoma cells induced osteoclast formation. ARL4C elevation in ameloblastoma further promoted its formation capabilities through the increased RANKL expression of mouse bone marrow cells and/or primary osteoblasts. These results suggest that the RAF1–MEK/ERK–ARL4C axis, which may function in cooperation with the BRAFV600E–MEK/ERK pathway, promotes ameloblastoma development. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.